sFlt-1 Is an Independent Predictor of Adverse Maternal Outcomes in Women With SARS-CoV-2 Infection and Hypertensive Disorders of Pregnancy - Hernandez-Pacheco, Jose Antonio; Torres-Torres, Johnatan; Martinez-Portilla, Raigam Jafet; Solis-Paredes, Juan Mario; Estrada-Gutierrez, Guadalupe; Mateu-Rogell, Paloma; Nares-Torices, Miguel Angel; Lopez-Marenco, Mario Enmanuel; Escobedo-Segura, Keren Rachel; Posadas-Nava, Alejandro; Villafan-Bernal, Jose Rafael; Rojas-Zepeda, Lourdes; et al. (Frontiers in Medicine, 2022)
Background Preeclampsia (PE) and COVID-19 share a common vascular–endothelial physiopathological pathway that may aggravate or worsen women's outcomes when both coexist. This study aims to evaluate the association of sFlt-1 levels and adverse maternal outcomes among positive SARS-CoV-2 pregnant women with and without hypertensive disorders of pregnancy (HDP). Methods We performed a multicenter retrospective cohort study of pregnant women with confirmed SARS-CoV-2 infection that required hospital admission. The exposed cohort comprised women with a diagnosis of an HDP. The primary outcome was a composite definition of adverse maternal outcome. The association between predictors and the main and secondary outcomes was assessed using an elastic-net regression which comprised a Lasso and Ridge regression method for automatic variable selection and penalization of non-statistically significant coefficients using a 10-fold cross-validation where the best model if automatically chosen by the lowest Akaike information criterion (AIC) and Bayesian information criteria (BIC). Results Among 148 pregnant women with COVID-19, the best predictive model comprised sFlt-1 MoMs [odds ratio (OR): 5.13; 95% CI: 2.19–12.05], and HDP (OR: 32.76; 95% CI: 5.24–205). sFlt-1 MoMs were independently associated with an increased probability of an adverse maternal outcome despite adjusting for HDP. Conclusions Our study shows that sFlt-1 is an independent predictor of adverse outcomes in women with SARS-CoV-2 despite hypertension status.